The history of marriage equality in Ireland : a social revolution begins - Tiernan, Sonja (Manchester University Press, 2020)
Tracing the campaign for marriage equality, this book highlights how this movement and the related referendum result have propelled Ireland from a country perceived as one repressed and controlled by the Catholic church to a country that is now admired as a leader in equality of human rights.